Age and anti-Műllerian hormone: prediction of cumulative pregnancy outcome in in vitro fertilization with diminished ovarian reserve - Yu Deng; Zhan-Hui Ou; Min-Na Yin; Pei-Ling Liang; Zhi-Heng Chen; Abraham Morse; Ling Sun (IMR Press, 2021)
Background: To determine the effects of AMH and age on IVF outcomes in women with DOR and whether the cumulative pregnancy potential after consecutive IVF cycles is age or AMH level depended. Methods: Between January 2014 and December 2018, 466 infertility patients (1004 IVF/ICSI cycles) with AMH ≤1.1 ng/mL were recruited and firstly divided into two groups (Group 1: AMH <0.6 ng/mL and Group 2: AMH 0.6-1.1 ng/mL). Furthermore, they were stratified into another four groups (A1, A2; B1, B2) based on age (Group A: <38 y, Group B: ≥38 y). Laboratory parameters and cumulative pregnancy chances were retrospectively evaluated. Results: Regardless of age, number of retrieved oocytes, 2 pronuclear zygotes (2PN), embryos, good-quality embryos per cycle, implantation rate (IR), clinical pregnancy rate (CPR) and ongoing pregnancy rate (OPR) per embryo transfer (ET) and per patient were significantly lower in Group 1 than those in Group 2 (P < 0.001). However, in women <38 years, there were no significant differences in IR, CPR and OPR per ET and per patient between Group A1 and A2 (P > 0.05). The cumulative OPR per patient increased to 60% in Group A2 and 51.7% in Group A1 after the third transfer but reached a plateau (24.8% in Group B2 and 11.8% in Group B1) after the second ET. Conclusions: For advanced-age women with DOR, AMH level showed as a strong predictor of both ovarian response and pregnancy rate. However, even with extremely lower AMH value, younger women still had higher potential to get pregnancy chance through more attempts at subsequent IVF treatments.